Engine Performance, Exhaust Emission And Combustion Analysis Of A 4-Stroke Spark Ignited Engine Using Dual Fuel Injection - D., Ramasamy (Elsevier Ltd, 2017)

(untitled)
The world natural gas reserve is plentiful. Instead of using gasoline to power ground vehicles, usage of Compressed Natural Gas (CNG) can improve the environment and reduce energy cost. However, most engines that runs on CNG are converted from gasoline based engine. Hence, the engines are not optimized for CNG. Other problems of converted engines are loss of power due to slower burn rate of CNG and gas displacement effect of CNG, hotter exhaust gas which degrade engine’s reliability, low mileage per tank and higher NOx. Since, converted engines are gasoline base engine, a dual fuel injection engine system can be developed to reduce the stated problems. Are activity controlled approach was incorporated where both gasoline and CNG are mixed before going into the combustion chamber. With this technique, when a blend of high reactive 35% gasoline and 65% CNG was used, the engine had its engine performance such torque, power and efﬁciency increasing by 10%. Also, the engine emissions such as hydrocarbon was reduced by 50% and carbon monoxide emission was reduced by 75% and NOx emission was reduced by 50% when compared with CNG baseline. Combustion of spark ignition engines converted to bi-fuel CNG is unstable and proper air and fuel mixing strategy is a concern here.